Simultaneous Large Optical and Piezoelectric Effects Induced by Domain Reconfiguration Related to Ferroelectric Phase Transitions. Issue 7 (5th January 2022) - Finkel, Peter; Cain, Markys G.; Mion, Thomas; Staruch, Margo; Kolacz, Jakub; Mantri, Sukriti; Newkirk, Chad; Kavetsky, Kyril; Thornton, John; Xia, Junhai; Currie, Marc; Hase, Thomas; et al.
Abstract: Electrical switching of ferroelectric domains and subsequent domain wall motion promotes strong piezoelectric activity, however, light scatters at refractive index discontinuities such as those found at domain wall boundaries. Thus, simultaneously achieving large piezoelectric effect and high optical transmissivity is generally deemed infeasible. Here, it is demonstrated that the ferroelectric domains in perovskite Pb(In1/2 Nb1/2 )O3 –Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 domain‐engineered crystals can be manipulated by electrical field and mechanical stress to reversibly and repeatably, with small hysteresis, transform the opaque polydomain structure into a highly transparent monodomain state. This control of optical properties can be achieved at very low electric fields (less than 1.5 kV cm −1 ) and is accompanied by a large (>10 000 pm V −1 ) piezoelectric coefficient that is superior to linear state‐of‐the‐art materials by a factor of three or more. The coexistence of tunable optical transmissivity and high piezoelectricity paves the way for a new class of photonic devices. Abstract : In domain‐engineered relaxor ferroelectric crystals of Pb(In1/2 Nb1/2 )O3 –Pb(Mg1/3 Nb2/3 )O3 –PbTiO3, reversible and repeatable phase transitions from the as‐poled polydomain rhombohedral state to a monodomain monoclinic state can be stimulated by electric field or stress. These transitions lead to bimodal functionality—variable optical transparency as well as a giant effective piezoelectric effect.